The Role Of Online Post-Sale Service Toward Repurchase Intention And Word Of Mouth - Nine Primastita Arif; Rizky Lux; Yahya Chusna Arif (Cakrawala Repositori IMWI, 2023)
Considering that e-commerce has become a major requirement, e-commerce providers must improve their products and services. After-sales service is one that must be considered to reduce customer doubts in using e-commerce. The purpose of this study was to investigate the role of e-commerce after-sales service (product returns, exchanges, and maintenance) on customer attitudes (relationship building) and behavioral aspects (developing customer repurchase intentions and word of mouth). This study used a judgemental sampling method in which 255 samples that met the requirements were adjusted to certain criteria. Structural Equation Model (SEM) supported by SmartPLS software is used to analyze the data. The findings in this study are that product returns and maintenance services have a significant effect on online customer satisfaction and satisfaction has a significant effect on customer trust. While product value has no significant effect on customer satisfaction. Customer satisfaction and trust, as indicators of relationship quality mediate the relationship between after-sales service (product returns, exchanges and maintenance), online customer repurchase intentions and WOM. Repurchase intention and WOM are positively influenced by trust and satisfaction. The research implications will be useful for policy makers, researchers, and the e-commerce industry in implementing and promoting the use of e-commerce.